2014
DOI: 10.4236/ajps.2014.519301
|View full text |Cite
|
Sign up to set email alerts
|

<i>In Vitro</i> Ovicidal and Larvicidal Activities of Stem Bark of <i>Terminalia glaucescens</i> (Combretaceae) against <i>Haemonchus contortus</i>

Abstract: Objectives: To evaluate the in vitro activity of aqueous and methanolic extracts of stem bark of Terminalia glaucescens on the eggs and larval stages of Haemonchus contortus of sheep. Methods: The eggs were exposed for 24 hours in five different concentrations (625, 1250, 2500, 3750 and 5000 µg/ml) of methanol, hot water (decoction) and cold water extracts at room temperature (25˚C). Distilled water, 1.25% DMSO and Albendazole were used as negatives and positive control respectively in the bioassay. Results: A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 11 publications
(14 reference statements)
0
2
0
Order By: Relevance
“…Indeed, Perry (2002) showed that condensed tannins would be able to bind to the lipoproteins of the eggshell membrane to inhibit osmotic pressure in egg, thus compromising hatching. According to Lem et al (2014), the condensed tannins would be able to penetrate the nematode cuticle and prevent the absorption of glucose, or block the post-synaptic receptors, thus paralyzing the larvae. On adult worms, condensed tannins would act on the digestive epithelium of the parasite to inhibit the functions of nutrition and lead to the death of the latter (Min et al, 2003).…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, Perry (2002) showed that condensed tannins would be able to bind to the lipoproteins of the eggshell membrane to inhibit osmotic pressure in egg, thus compromising hatching. According to Lem et al (2014), the condensed tannins would be able to penetrate the nematode cuticle and prevent the absorption of glucose, or block the post-synaptic receptors, thus paralyzing the larvae. On adult worms, condensed tannins would act on the digestive epithelium of the parasite to inhibit the functions of nutrition and lead to the death of the latter (Min et al, 2003).…”
Section: Resultsmentioning
confidence: 99%
“…Te active compound may inhibit the transmission of nervous impulses by gamma-aminobutyric acid (GABA) whose secretion is stimulated by the active compound [23]. Lem et al [24] mentioned that active compounds found in food can cross the intestinal lining of larvae and gain access to the circulatory system of the organism. Moreover, active compounds like tannin may bind to the cuticle of the nematode, destabilize the membrane, and increase cell permeability by combining with membrane-associated sterols which lead to death [25].…”
Section: Discussionmentioning
confidence: 99%